Import substitution as an effective tool for the development of Russian economy - O. М. Javadova; S. М. Gasankadieva (Вестник Северо-Кавказского федерального университета)
Introduction. This article explores the topic of import substitution as a tool for the development of national economy. In modern conditions, when global changes are taking place on the world market, Russia faces the need to reduce dependence on imports and develop domestic production. Various aspects of import substitution are considered, including its concepts, factors influencing its development, and methods that can be used to stimulate the localization of production. Materials and methods. The article examines the main reasons that caused the need for import substitution in Russia, and also analyzes the measures taken by the government to solve this problem. The results of the conducted research in this area will be analyzed, and recommendations for the further development of the import substitution strategy in Russia will be presented. Research and discussion. The main results of the study show that import substitution can become a key factor for the development of the Russian economy. It can lead to an increase in local production, a decrease in dependence on imports and an increase in economic security. To achieve these results, it is necessary to consider various measures to stimulate import substitution, such as the development of national production capabilities, the promotion of innovation, infrastructure improvements and preferential tax regulation. Conclusion. Based on the analysis, it can be concluded that import substitution is an effective tool for the development of national economy, but its implementation requires a comprehensive strategy that takes into account both economic and political aspects of this program.